(untitled) (Agro Productividad, 2022)
Objective: To characterize the goat producers according to the industrial destinations of the milk, in order to analyze the coordination mechanisms established in the agri-food chain. Design/Methodology/Approach: A survey was applied to 122 randomly selected goat producers. Taking into account two industrial destinations, a socioeconomic, productive, and commercial comparison was carried out, through T-tests for independent means. In order to analyze the coordination mechanisms, the data were complemented interviewing owners of collection centers and businessmen who processed milk. Results: The producers had small herds and a basic level of education. They used family workforce. The lack of organization in the sale limited their participation in the agri-food chain coordination. Milk processing companies coordinate their efforts, organizing the collection, reaching trade agreements, setting prices, and establishing quality rules, usually through informal agreements. Limitations/Implications: State intervention is necessary to regulate relations between the actors of the agri-food chain. Findings/Conclusions: The informality of coordination mechanisms favors agribusiness and turns them into forms of domination that ensure their profitability